Religious actions speak louder than words: exposure to credibility-enhancing displays predicts theism. Issue 1 (2nd January 2017) - Lanman, Jonathan A.; Buhrmester, Michael D.
ABSTRACT: One of the central aims of the cognitive science of religion (CSR) is to explain why supernatural agent beliefs are so widespread. A related but distinct aim is to explain why some individuals hold supernatural agent beliefs but others do not. Here, we aim to provide an initial test of the power of exposure to what Henrich calls "credibility-enhancing displays" (or "CREDs") in determining whether or not an individual holds explicit supernatural agent beliefs. We present evidence from two studies of Americans suggesting that exposure to CREDs, as measured by a scale we developed and validated, predicts current theism vs. non-theism, certainty of God's existence/non-existence, and religiosity while controlling for overall religious socialization. These results are among the first to empirically support the theorized significance of CREDs for the acquisition of supernatural agent beliefs.